An Adaptive Re-use of Cultural Heritage Buildings in Jabodetabek (Greater Jakarta) as the National Gallery of Indonesia's Satellites - Yuke Ardhiati; Ashri Prawesthi D; Diptya Anggita; Ramadhani Isna Putri; L Edhi Prasetya; Widya Nur Intan; Muhammad Wira Abi; Rafli Alfiano; Muhammad Rifqie Izzulhaq; Raditia Raka Putra; Chandra Arfiansyah (Department of Architecture Universitas Muhammadiyah Jakarta, 2020)
The Nasional Gallery of Indonesia is a reputable art gallery owned by Indonesian State. It roles as the venue for exhibitions and art events on International scale. To maintain the reputation then it employed the Independent Curators to cary out exhibitions. In recent years, the phenomenon of the proffesional Fine Art Artists show the hing spirits. To enrich their international publication then they began to realize their opportunity to exhibit at this gallery. Unfortunately, the gallery building is an adaptive reuse of the Cultural Heritage Building. The National Gallery building which has a distinctive Dutch Colonial architectural style has not been optimally utilized. So, it has existence has wide limitations and space limitation that unable to accommodate such high interests. On the other hand, Jabodetabek is stands for Jakarta-Bogor-Depok-Tangerang-Bekasi are the Greater City of Jakarta, has Cultural Heritage Buildings. There are many of architectural style of heritage buildings that has chance to be the exhibition spaces. The study is an idea to aim solutions of the availability of exhibition area in Jabodetabek to accommodate the Fine Art Artists interest of exhibiting. According to the Adaptive-Reuse of the National Gallery’s case, and by refers to the Grounded Theory Research method and Case Studies related to the Jabodetabek’s Cultural Heritage buildings. A Working Hyphotesis is Jabodetabeks’s Cultural Heritage Buildings opportunities as The National Gallery’s Satellites. The findings are the Satellite Galleries Rank, and the Properties Display recommendation based on the Cultural Heritage’s rules that can be offered to make them as the “Satellite” as well as the ICOM as the National Gallery of Indonesia’s standard.